Identities involving squares of sines and cosines of multiples or submultiples of the angles involved.
To prove the identities involving squares sines and cosines we use the following algorithm.
Step I: Arrange the terms on the on the L.H.S. of the identity so that either sin\(^{2}\) A - sin\(^{2}\) B = sin (A + B) sin (A - B) or cos\(^{2}\) A - sin\(^{2}\) B = cos (A + B) cos (A - B) can be used.
Step II: Take the common factor outside.
Step III: Express the trigonometric ratio of a single angle inside the brackets into that of the sum of the angles.
Step IV: Use the formulas to convert the sum into product.
Examples on Identities involving squares of sines and
cosines:
1. If A + B + C = π, prove that,
sin\(^{2}\) A + sin\(^{2}\) B + sin\(^{2}\) C = 2 + 2 cos A cos B cos C.
Solution:
L.H.S. = sin\(^{2}\) A + sin\(^{2}\) B + sin\(^{2}\) C
= \(\frac{1}{2}\)(1 - cos\(^{2}\) A) + \(\frac{1}{2}\)( 1- cos\(^{2}\) B) + 1- cos\(^{2}\) C
[Since, 2 sin\(^{2}\) A = 1 - cos 2A
⇒ sin\(^{2}\) A = \(\frac{1}{2}\)(1 - cos 2A)
Similarly, sin\(^{2}\) B = \(\frac{1}{2}\)(1 - cos 2B) ]
= 2 - \(\frac{1}{2}\)(cos 2A + cos 2B) - cos\(^{2}\) C
= 2 - \(\frac{1}{2}\) ∙ 2 cos (A + B) cos (A - B) - cos\(^{2}\) C
= 2 + cos C cos (A - B) - cos\(^{2}\) C, [Since, A + B + C = π ⇒ A + B = π - C.
Therefore, cos (A + B) = cos (π - C) = - cos C]
= 2 + cos C [cos (A - B) - cosC]
= 2 + cos C [cos (A - B) + cos (A + B)], [Since, cos C = cos (A + B)]
= 2 + cos C [2 cos A cos B]
= 2 + 2 cos A cos B cos C = R.H.S. Proved.
2. If A + B + C = \(\frac{π}{2}\) prove that,
cos\(^{2}\) A+ cos\(^{2}\) B + cos\(^{2}\) C = 2 + 2sin A sin B sin C.
Solution:
L.H.S. = cos\(^{2}\) A+ cos\(^{2}\) B + cos\(^{2}\) C
= \(\frac{1}{2}\)(1+ cos 2A) + \(\frac{1}{2}\)(1 + cos 2B)+ cos\(^{2}\) C [Since, 2 cos\(^{2}\) A = 1 + cos 2A
⇒ cos\(^{2}\)A = \(\frac{1}{2}\)(1 + cos2A)
Similarly, cos\(^{2}\)B =\(\frac{1}{2}\)(1 + cos 2B)]
= 1 + \(\frac{1}{2}\)(cos 2A + cos 2B) + cos\(^{2}\) C
= 1+ \(\frac{1}{2}\) ∙ [2 cos (A + B) cos (A - B)] + 1- sin\(^{2}\) C
= 2 + sin C cos (A - B) - sin\(^{2}\) C
[A + B + C = \(\frac{π}{2}\)
⇒ A + B = \(\frac{π}{2}\) - C
Therefore, cos (A + B) = cos (\(\frac{π}{2}\) - C)= sin C]
= 2 + sin C [cos (A - B) - sin C]
= 2 + sin C [cos (A - B) - cos (A + B)], [Since, sin C = cos (A + B)]
= 2 + sin C [2 sin A sin B]
= 2 + 2 sin A sin B sin C = R.H.S. Proved.
● Conditional Trigonometric Identities
11 and 12 Grade Math
From Identities Involving Squares of Sines and Cosines to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
May 19, 24 06:35 PM
May 19, 24 03:36 PM
May 19, 24 03:19 PM
May 19, 24 02:23 PM
May 19, 24 01:26 PM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.